The importance and value of reporting guidance for scoping reviews: A rehabilitation science example - Miller, Erin; Colquhoun, Heather (Australian journal of advanced nursing, 2020)
Objective: Scoping reviews use a systematic approach to synthesize a body of knowledge. The use of scoping review methodology is increasingly common. Despite recommendations to guide the conduct of scoping reviews, inconsistencies exist with regards to their methodology and reporting. In this case-study, we reflect on our experience using the PRISMA Extension for Scoping Reviews (PRISMAScR): Checklist and Explanation to improve reporting for a scoping review we initially conducted prior to the release of the PRISMA-ScR reporting guidelines. Study Design and Methods: We evaluated the scoping review against 22 criteria included in the PRISMA-ScR. For each criterion, we provided a rating representing the degree to which we felt the scoping review met the individual criterion in the PRISMAScR. We also provided comments to substantiate our ratings, along with recommended revisions for the scoping review and considerations for future scoping reviews. Results: We identified a number of strengths in the initial reporting of our scoping review , as well as opportunities for improvement. The most substantial areas for improvement included the protocol registration, data items and data charting process. Based on our evaluation, we made revisions to the scoping review manuscript to improve our reporting. Conclusion: Our evaluation helps to highlight the value of using reporting guidelines to improve reporting of scoping reviews, while also exposing several challenges. In future, we recommend consulting the guidelines during the initial preparation of the scoping review manuscript rather than retrospectively. What is already known about the topic? - The use of scoping review methodology is becoming increasingly common. - While recommendations to guide the conduct of scoping reviews have been published, inconsistencies exist in both scoping review methodology and reporting. What this paper adds: - Despite some challenges, we found the PRISMAScR to be an effective tool to guide a structured reflection on our scoping review reporting. - We encourage authors completing scoping reviews to make use of the PRISMA-ScR to guide their own scoping review reporting.